(Invited) Simulation Study of High Voltage Vertical GaN Nanowire Field Effect Transistors. (17th August 2017) - Sabui, Gourab; Zubialevich, Vitaly Z.; Pampili, Pietro; White, Mary; Parbrook, Peter J.; McLaren, Mathew; Arredondo-Arechavala, Miryam; Shen, Z. John
Abstract : Concept of vertical Gallium Nitride (GaN) nanowire field effect transistors (NWFETs) for high voltage power electronic applications is investigated through three dimensional (3D) TCAD simulations in this paper. The proposed GaN NWFET can operate either in a normally-off or a normally-on mode depending on the specific device design. A gate-all-around (GAA) structure coupled with a strong dielectric REduced SURface Field (RESURF) effect has the potential to offer blocking voltages over 900 V with very low specific on-resistance for the NWFETs. VRB 2 /RON and QGD x RDS(ON) Figures of Merits (FoMs) of the NWFET are extracted and compared with other state of the art GaN, SiC and Si field effect transistors to get a comparative understanding of the potential of the NW architecture for high voltage applications.